How do A‐train sensors intercompare in the retrieval of above‐cloud aerosol optical depth? A case study‐based assessment. Issue 1 (15th January 2014) - Jethva, Hiren; Torres, Omar; Waquet, Fabien; Chand, Duli; Hu, Yongxiang
Abstract We intercompare the above‐cloud aerosol optical depth (ACAOD) of biomass burning plumes retrieved from A‐train sensors, i.e., Moderate Resolution Imaging Spectroradiometer (MODIS), Cloud‐Aerosol Lidar with Orthogonal Polarization (CALIOP), Polarization and Directionality of Earth Reflectances (POLDER), and Ozone Monitoring Instrument (OMI). These sensors have shown independent capabilities to retrieve aerosol loading above marine boundary layer clouds—a kind of situation often found over the southeast Atlantic Ocean during dry burning season. A systematic comparison reveals that all passive sensors and CALIOP‐based research methods derive comparable ACAOD with differences mostly within 0.2 over homogeneous cloud fields. The 532 nm ACAOD retrieved by CALIOP operational algorithm is underestimated. The retrieved 1064 nm AOD however shows closer agreement with passive sensors. Given the different types of measurements processed with different algorithms, the reported close agreement between them is encouraging. Due to unavailability of direct measurements above cloud, the validation of satellite‐based ACAOD remains an open challenge. The intersatellite comparison however can be useful for the relative evaluation and consistency check.